Manajemen Waktu Santri Tahfidz Dar al-Furqon Desa Janggalan Kecamatan Kota Kabupaten Kudus (Kajian Surah Al-Ashr Dalam Tafsir Al-Misbah) - Nisa, Mir'atun (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
This study describes the time management of students in Daar al-Furqon Islamic boarding school in memorizing the Qur'an. Santri Daar al-Furqon made good use of time in accordance with the schedule of Islamic boarding school activities. In surah al-Ashr explaining the importance of time, students who memorize the Qur'an must use their time well so that they do not become losers. The purpose of this study was to determine how the time division of santri tahfidz Daar al-Furqon Janggalan, Kota, Kudus. And the use of time in accordance with the interpretation of Surah al-Ashr in the interpretation of al-Misbah relating to time management. Research using field research methods with a qualitative approach. Data collection uses observation, interview, and documentation techniques. While the data analysis is done through data reduction, data display, and drawing conclusions or data verification. The results showed that given the importance of time and loss for people who waste their time and use their time properly in accordance with the schedule in the boarding school. And every student must have time management so that they can utilize memorization time well, by running time management students can get good results from the work done.